2016
DOI: 10.1111/cen.13115
|View full text |Cite
|
Sign up to set email alerts
|

Implications of oncocytic change in papillary thyroid cancer

Abstract: SummaryObjective Although the presence of oncocytic change in less than 75% of a tumour is not considered to indicate oncocytic variants of papillary thyroid carcinoma (PTC), we frequently observe partial oncocytic change, especially in obese PTC patients. Thus, we sought to investigate the relationship between the presence of oncocytic change of PTC and its prognosis. Design, setting and participants We retrospectively studied 142 patients with PTC who had undergone surgery between 2000 and 2005, and re-evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Warthin‐like variant PTC shares histological features with Warthin tumor of salivary gland origin, and the prognosis is similar with that of conventional PTC . Oncocytic variant PTC was reported to have a higher tumor recurrence rate (28% vs 11%) and cause‐specific mortality (17% vs 4%) than conventional PTC, and this was confirmed in a Korean patient cohort (recurrence rates, 30.8% vs 11.7%) by Hong et al …”
Section: Oncocytic Variant Ptc and Warthin‐like Variantmentioning
confidence: 75%
See 2 more Smart Citations
“…Warthin‐like variant PTC shares histological features with Warthin tumor of salivary gland origin, and the prognosis is similar with that of conventional PTC . Oncocytic variant PTC was reported to have a higher tumor recurrence rate (28% vs 11%) and cause‐specific mortality (17% vs 4%) than conventional PTC, and this was confirmed in a Korean patient cohort (recurrence rates, 30.8% vs 11.7%) by Hong et al …”
Section: Oncocytic Variant Ptc and Warthin‐like Variantmentioning
confidence: 75%
“…Warthin-like variant PTC shares histological features with Warthin tumor of salivary gland origin, and the prognosis is similar with that of conventional PTC. 1,56 Oncocytic variant PTC was reported to have a higher tumor recurrence rate (28% vs 11%) and cause-specific mortality (17% vs 4%) than conventional PTC, 151 and this was confirmed in a Korean patient cohort (recurrence rates, 30.8% vs 11.7%) by Hong et al 152 The Warthin-like variant was included in oncocytic variant PTC in the previous WHO classification, and was regarded The PTC variants with fibromatosis/fasciitis-like stroma, spindle cell and clear cells are rare, and the prevalence of such variants was 0.06% (1/1521) for fibromatosis/fasciitislike stroma, 0% for spindle cell and 0.06% (1/1521) for clear cell variant PTC in a Japanese patient cohort reported by Ito et al 153 ( Table 2). They are low-risk PTC similar with conventional PTC, and no definite prognostic information is available.…”
Section: Oncocytic Variant Ptc and Warthin-like Variantmentioning
confidence: 90%
See 1 more Smart Citation
“…Oncocytic follicular cells are also seen in the oncocytic variant of papillary thyroid carcinoma, which is a rare subtype of papillary thyroid carcinoma. Variable biological behaviors have been reported for the oncocytic variant of papillary thyroid carcinoma, which is histologically defined by the presence of oncocytes (at least 75% of the entire tumor) seen along with the classic nuclear features of papillary thyroid carcinoma 25…”
Section: Hürthle Cell Cytology Genotype and Clinical Behaviormentioning
confidence: 99%
“…Therefore, early diagnosis and treatment is of great significance to prolong patient survival. The discovery of potential therapeutic target in the basic research is particularly important (Hong et al, 2016). In recent years, it has been shown that miRNAs play important roles in a variety of diseases.…”
Section: Discussionmentioning
confidence: 99%